Immune checkpoints in rheumatoid arthritis: progress and promise - Small, Annabelle; Lowe, Katie; Wechalekar, Mihir D. (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is one of the most prevalent autoimmune inflammatory conditions, and whilst the mechanisms driving pathogenesis are yet to be completely elucidated, there is a clear role for self-reactive T cells and the involvement of immune checkpoint pathways. In this review, we provide an overview of the importance of checkpoint pathways in the T cell response and describe the involvement of these in RA development and progression. We discuss the relationship between immune checkpoint therapy in cancer and autoimmune adverse events, draw parallels with the involvement of immune checkpoints in RA pathobiology, summarise emerging research into some of the lesser-known pathways, and the potential of targeting checkpoint-related pathways in future treatment approaches to RA management.